ANALISIS HUKUM PEMBERIAN REHABILITASI KEPADA MANTAN DIREKSI ASDP DALAM PERKARA KORUPSI BERDASARKAN PUTUSAN NOMOR 68/Pid.Sus-TPK/2025/PN JAKARTA PUSAT - Dianto, Femas Rama; Nugroho, Sigit Sapto; Pradhana, Angga Pramodya (Jurnal Ilmiah Dinamika Hukum, 2026)
This study aims to analyze the laws and regulations related to the granting of rehabilitation by the president in relation to corruption committed by former ASDP directors, which has been declared to have caused financial losses to the state amounting to Rp.1.25 trillion. The researcher conducted research using normative legal research methods with a legislative approach and a case approach. Legal sources were obtained from primary, tertiary, and secondary sources related to the legal analysis of the president in granting rehabilitation to former directors of ASDP Indonesia Ferry. The researchers identified two research questions: what considerations did the president take into account in granting rehabilitation to the former director of ASDP Indonesia Ferry, and what are the legal consequences of granting rehabilitation to the former director of ASDP Indonesia Ferry. In granting rehabilitation, the president must seek the opinion of the Supreme Court. The granting of rehabilitation by the president is based on the aspirations of the people as conveyed to the House of Representatives and must be proven not to be detrimental to state finances. One judge disagreed because he considered it to be purely a business mistake. Keywords: Rehabilitation, Corruption Crimes, ASDP